Genetic analysis of selected body measurements of Hungarian Sport Horse mares - Posta, János; Komlósi, István (Acta Agraria Debreceniensis, 2007)
The authors made their analysis based on the body measurements of 3080 Hungarian Sport Horse mares listed in the Hungarian Sport Horse Studbook. Height at withers by stick, height at withers by tape, heart girth and cannon-bone circumference were measured in Hungarian Sport Horse mare performance tests.Phenotypic correlations among height at the withers and heart girth and cannon-bone circumference varied within a range of 0.45-0.55. There was close genetic correlation (r=0.63-0.82) between the body measurement traits. Heritability values were moderate for height at withers by stick, height at withers by tape and heart girth (h2=0.31-0.49). There were high heritability values (h2=0.51) for cannon-bone circumference.There were low phenotypic correlations between frame (as conformational trait) and height at the withers (measured by tape and stick) and heart girth.